Vertically perforated clay brick masonry for loadbearing and non-loadbearing masonry walls - Lourenço, Paulo B. (2010)
The work presented in this paper deals with the development of a solution for structural masonry walls to be used in zones with different seismic hazard and also a solution for enclosure walls for replacement of traditional cavity walls. A key concern on modern construction is sustainability, particularly with respect to energy efficient buildings, as energy consumption of buildings represents a significant share of the total consumption of energy. The novel clay masonry unit proposed here ensures an appropriate thermal and mechanical performance. Besides the description of the optimization process to obtain a proper thermal performance, the paper addresses mechanical validation based on a set of experimental tests carried out on units and masonry walls under uniaxial compressive loading. Additionally, a set of in-plane cyclic tests were carried out on masonry walls in order to assess the performance of the system under seismic loading. The results indicate that the proposed masonry unit leads to adequate thermal and mechanical behavior.